The Coronavirus Pandemic and Immigrant Communities: A Crisis That Demands More of the Social Work Profession. Issue 1 (February 2021) - Cross, Fernanda L.; Gonzalez Benson, Odessa
As the coronavirus pandemic has taken over matters of life and death globally, immigrant communities were some of the most deeply impacted. In the United States (U.S.), Latinx immigrants and other minorities have experienced greater economic burden and worse health outcomes, resulting in alarming rates of death from COVID-19. Yet the government's relief measures to support individuals did not extend to millions of immigrants. This left many immigrants with the cruel choice to either stay home to protect themselves and their loved ones from the virus or go to work to support their families. Disregard for a large segment of the population is further complemented by strict immigration policies, harsher border restrictions, and public health guidelines that failed to account for the realities faced by immigrants. In this brief, we highlight the unequal toll of the COVID-19 pandemic on immigrants and consider social work response. We argue that the pandemic demands more of the social work profession, as the coronavirus crisis exposed more clearly the systemic inequalities toward immigrants and aggravates their vulnerabilities. Insofar as systems are unequal and racist in the context of coronavirus, there is a great need for social work response that is innovative, brave, and deeply connected to communities.